2008
DOI: 10.2337/dc07-2185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Glulisine on Microvascular Blood Flow and Endothelial Function in the Postprandial State

Abstract: OBJECTIVE -To investigate the effect of insulin glulisine on postprandial microvascular blood flow in type 2 diabetes.RESEARCH DESIGN AND METHODS -A total of 15 patients with type 2 diabetes received insulin glulisine or human insulin before a liquid meal test. Thereafter, skin microvascular blood flow was measured by laser Doppler fluxmetry and blood samples were taken for measurement of plasma levels of glucose, insulin, intact proinsulin, asymmetric dimethylarginine, nitrotyrosine, interleukin-18, matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(23 reference statements)
2
9
0
1
Order By: Relevance
“…In later stage diabetes, high-dose insulin treatment in an insulin-resistant state results in activation of mitogen-activated protein kinase with consecutive endothelin I secretion and development of atherosclerosis by binding to the same receptor 22,23 . We have been able to demonstrate that the kinetics of exogenously administered insulin has a major influence on the vascular action of this hormone and that a faster onset of action is associated with improvement of microcirculation and associated time courses of nitrotyrosine and other biomarkers of oxidative stress and atherosclerosis risk 8,24,25 . In consequence, insulin can be regarded as a bipotential hormone having positive or negative impact on vascular function, dependent on the time-action profile of the administered insulin and the stage of insulin resistance of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…In later stage diabetes, high-dose insulin treatment in an insulin-resistant state results in activation of mitogen-activated protein kinase with consecutive endothelin I secretion and development of atherosclerosis by binding to the same receptor 22,23 . We have been able to demonstrate that the kinetics of exogenously administered insulin has a major influence on the vascular action of this hormone and that a faster onset of action is associated with improvement of microcirculation and associated time courses of nitrotyrosine and other biomarkers of oxidative stress and atherosclerosis risk 8,24,25 . In consequence, insulin can be regarded as a bipotential hormone having positive or negative impact on vascular function, dependent on the time-action profile of the administered insulin and the stage of insulin resistance of the individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its role in the regulation of glucose metabolism, insulin has been shown to mediate important vascular effects by stimulating the endothelial secretion of nitric oxide (5,16). Recent studies suggest that the pharmacokinetic profile of subcutaneous insulin absorption might have an impact on the generation of postprandial oxidative stress and the development of endothelial dysfunction (911,17). Insulin may directly affect the generation or degradation of ADMA, and insulin resistance is associated with increased ADMA levels (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…ADMA was chosen as the primary end point because a previous study had demonstrated a significant impact of fast-acting analogs on the generation of postprandial ADMA levels in patients with type 2 diabetes (10). A sample size of 14 patients was calculated to provide 80% power, assuming a comparable effect on the postprandial excursion of plasma ADMA levels and considering a two-sided test with a significance level of 5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular endothelium has been shown to play an important role in capillary recruitment by the release of NO. It has been shown that capillary recruitment by insulin also may occur in the skin (Hohberg et al, 2008) and that this process is impaired in hypertension, obesity and insulin resistance (de Jongh et al, 2004a;de Jongh et al, 2004b).…”
Section: Endothelial Dysfunction and Insulin Resistancementioning
confidence: 99%